(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2024)
The Point of view of Barru Society Towards Massappo Wanua Tradition. The purpose of this research is to find out the people’s views on the Massappo Wanua tradition in Binuang Village, Balusu District, Barru Regency. The author uses a qualitative method. The data sources for this research are the Village Head, Village Secretary, Traditional Stakeholders, and the people of Binuang Village, Baruu Regency, and several journals as support. Furthermore, the data collection method used is observation, interviews, and documentation. The results of this study indicate a form of expression of gratitude to the Creator. This tradition is carried out once a year at the beginning of the year. This tradition continues to this day because the local people believe in the ritual of cleaning the village and aims to protect the environment from disease, threats or disasters.